Design of a smart gadget to correct posture and relieve muscle discomfort on teleworkers - Araya-Canales, María I. (2022)
Due to the Covid 19 pandemic, telecommuting became one of the most important work modalities in the private and public sectors. Its benefits have been multiple economically speaking, however, it also brought disadvantages for users who needed to adapt the conditions of their home to this modality. These complications are especially muscle affectations in the neck and back areas, as a result of poor posture during the workday. From this, it was identified the need to help teleworkers to correct postural problems, reducing and preventing musculoskeletal pain, in a different way to what is found in the market where the products are focused only on warning, creating discomfort to the user. Therefore, it was proposed, through the design thinking methodology, the design of the smart gadget THÉSI, a product that allows the correction of posture through an alarm system with a silent mode, that reminds when the neck is flexed at an angle greater than 15° and offers a vibration system in points of tension to relax the back muscles. Thus, it was discovered that it is possible to improve the user's muscle memory by reminding them to readjust their posture when making an inappropriate angle and thus avoid forced postures, which prevents musculoskeletal injuries that can affect the quality of life, as well as making the teleworking experience itself more pleasant.